2018
DOI: 10.1155/2018/2061516
|View full text |Cite
|
Sign up to set email alerts
|

Medical Image Classification Based on Deep Features Extracted by Deep Model and Statistic Feature Fusion with Multilayer Perceptron

Abstract: Medical image classification is a key technique of Computer-Aided Diagnosis (CAD) systems. Traditional methods rely mainly on the shape, color, and/or texture features as well as their combinations, most of which are problem-specific and have shown to be complementary in medical images, which leads to a system that lacks the ability to make representations of high-level problem domain concepts and that has poor model generalization ability. Recent deep learning methods provide an effective way to construct an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 33 publications
0
85
0
Order By: Relevance
“…These deep learning technologies have also been applied to medical images. Examples include computed tomography image classification [10,11], feature extraction [12,13] and automatic detection of lung tumors [14,15], and automatic detection of breast tumors on X-ray images [16,17]. These machine-aided diagnostic techniques have supported the efforts of radiologists to achieve more accurate diagnoses and tumor detection.…”
Section: Introductionmentioning
confidence: 99%
“…These deep learning technologies have also been applied to medical images. Examples include computed tomography image classification [10,11], feature extraction [12,13] and automatic detection of lung tumors [14,15], and automatic detection of breast tumors on X-ray images [16,17]. These machine-aided diagnostic techniques have supported the efforts of radiologists to achieve more accurate diagnoses and tumor detection.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a network with just three convolution layers seems to be not sufficient for dealing with the complexity of the application at hand. The architecture of Arjmand et al [22] is shown in Figure 7.Lai et al [24] introduced a network with six convolution layers and no fully connected layers. This network achieved the best results, among the competitors of our proposed architecture, for both the optimizers.…”
mentioning
confidence: 99%
“…The differences between this network and our network are the size of the kernels used (which is higher than our proposed network), the absence of any regularization layers, the absence of any fully connected layers, and the number of convolutional layers, (which is higher in our model). The main difference in terms of design choices between the architecture of Lai et al [24] and our architecture is the absence of any regularization layers from their architecture. According to the experiments we performed, this seems to be the main cause for the lower performance of the network proposed by Lai and coauthors.…”
mentioning
confidence: 99%
See 2 more Smart Citations